Analysis of Science Literacy Skills in Science Subjects on Heat Material of Grade VII Students at Junior High School 10 Sampit - Setiawan, Ronny; Elhawwa, Tazkiyatunnafs (International Journal of Universal Education, 2025)
The results of the 2022 PISA (Paris-Pelaksanaan Sains Indonesia/PISA) show that Indonesian students' scientific literacy remains low, including in heat. This study aims to analyze the scientific literacy skills of seventh-grade students at Junior High School 10 Sampit regarding scientific knowledge and attitudes. The study used a descriptive quantitative method with a sample of 55 students. Data were obtained through a scientific literacy test and a scientific attitudes questionnaire, then analyzed using descriptive percentages. The results show that scientific literacy achievement in the knowledge aspect was 41.21% (very poor category) and in the scientific attitudes aspect was 69.92% (sufficient category). The highest level of knowledge was in content (43.33%) and the lowest in epistemic (36.36%), while the highest level of scientific attitudes was in understanding environmental issues (72.00%) and the lowest level in interest in science and technology (69.23%). The main influencing factors were interest in learning science, limited practical work, and lack of experience working on scientific literacy-based problems. These findings indicate the need to improve practice-based learning strategies and practice problems.